The Roles of Translators and Interpreters: Opportunities and Challenges in Translation and Interpreting Activity - Nur Fitria, Tira (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2024)
This research explores the roles of translators and interpreters in the 21st century, focusing on their differences in work methods, language type focus, context understanding, translation style, processing time, translator tool assistance, role in communication, and additional skills. This research is library research. The analysis shows that both professionals require a deep understanding of culture and language, expert knowledge, and clear communication. Translators must understand cultural knowledge for negotiations, while interpreters facilitate communication between people speaking different languages. They must consider non-verbal cues, and have excellent language skills, quick thinking, effective information processing, and in-depth knowledge of the culture and business practices associated with the languages they translate. Interpreters can use the SIS (Simultaneous Interpretation System) tool or not. In the 21st century, translation and interpretation are complex professions that require adaptability and diverse abilities to navigate globalization. Technical and non-technical factors influence translation continuity, with technical factors like sound systems and lighting affecting quality. Training programs for translators and interpreters have emerged, with certification being a key requirement for recognition.